A wideband circularly polarized antenna using mutual coupling method. Issue 1 (10th August 2017) - Yang, Long; Zhao, Chunliu; Chen, Xi; Zhang, Zhi‐Ya; Fu, Guang; Yan, Zehong
Abstract: A novel wideband circularly polarized (CP) antenna is presented in this article. The proposed antenna consists of a four‐leaf clover patch, four L‐probes, and wideband networks. Based on the tightly coupled mechanism, the four L‐probes are formed as a ring with the adjacent ones kept close for strong mutual coupling. Consequently, the proposed antenna realizes a wideband impedance matching. Meanwhile, the four‐leaf clover patch is put closely inside of the ring for further improving the impedance bandwidth, which is proximity‐coupled fed by the four sequential‐rotation L‐probes with phase of 0°, 90°, 180°, and 270°. The four L‐probes are connected to the respective ports of a wideband feeding network by a two‐stage impedance transforming network. The measured results indicate that the proposed design has an impedance bandwidth of 66.7% from 1.0 to 2.0 GHz for VSWR ≤ 2 and a 3‐dB axial ratio bandwidth of 56.5% from 1.08 to 1.93 GHz. Furthermore, in the operating bandwidth, stable and symmetry radiation patterns and high gain are obtained. The design has a 3‐dB gain bandwidth of 38% from 1.3 to 1.9 GHz with a peak gain of 8.5 dBic.